Navigating Work and Breastfeeding: A Qualitative Exploration of Breastfeeding Experiences among Nurses and Support Staff in South India - Limalemla Jamir; Desham Chelimela; Amrita Datta (Turkish Archives of Pediatrics)
Objective: The personal experiences of breastfeeding healthcare workers may influence the quality of breastfeeding support provided. This study explored the breastfeeding experiences of nurses and support staff in South India.